Pengaruh Dukungan Sosial terhadap Kecemasan pada Penyintas Covid-19 - Natasha Jordan; Maria Goretti Adiyanti (Kuras Institute, 2022)
Many people in Indonesia have been exposed to covid-19 since 2020. When suffering from covid-19, patients may experience some physical and psychological responses. Psychological responses experienced after being confirmed covid-19 are fear of clinical symptoms, inability to recover, becoming a burden to others, and fear of death. These responses can cause anxiety. This study aims to see the effect of social support on anxiety levels among Covid-19 survivors in Indonesia. This study uses a quantitative approach by analyzing the influence between variables. The subjects in this study were 396 covid-19 survivors from age 19 until 34 in Indonesia. Data collection using 20 items from Beck Anxiety Inventory (BAI) and 12 items from the Multidimensional Scale of Perceived Social Support (MSPSS). The data analysis uses simple linear regression. Based on the data analysis results, social support negatively affects anxiety levels among Covid-19 survivors when they are suffering from covid-19 (2.3%). At the same time, the other (97.7%) were influenced by other factors not measured in this study. This study also found that anxiety and social support didn’t significantly differ with gender, age, area, duration of exposure to covid-19, and treatment place.